THE CONNECTIONS BETWEEN THE EVOLUTION OF VEGETATION COVER IN THE SOUTHERN ARAL SEA REGION AND THE TRANSPORT OF SALTS FROM THE DESICCATED SEABED OF THE ARAL SEA (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This article examines quantitative changes in the vegetation cover of the Southern Aral Sea region as a whole, caused by the long-term impact (1961–2024) of salt transport from the dried-up Aral Sea bed. Excluding species transformations, the evolution of vegetation cover is considered here in terms of the reduction in areas covered by vegetation. Using modeling methods, the study aggregates the spatio-temporal dynamics of the total projected vegetation cover in relation to the average annual sulfate deposition from the Aralkum Desert. The research results are presented as formalized patterns of vegetation degradation and as cartographic representations of salt deposition fields from the dried seabed and the corresponding changes in total projected cover by decades from 1961 to 2024. The impact of salt transport is determined by dust deposition on plant root zones and by increasing soil salinity.